Public acceptance of the use of drones for logistics: The state of play and moving towards more informed debate. (February 2022) - Smith, Angela; Dickinson, Janet E.; Marsden, Greg; Cherrett, Tom; Oakey, Andrew; Grote, Matt
Abstract: Policy makers are keen to understand public and stakeholder concerns in relation to the greater deployment of drones within transport systems and studies have sought to quantify public acceptance of drones with common themes including worries relating to privacy and safety and a lack of engagement with the technology amongst some demographic groups. This paper critically examines the research on public acceptance of drones finding the conflation of a diverse range of drone applications has led to ambiguity in the prevailing concerns and that the absence of clear parameters for drone use in local transport environments limits scope to develop informed opinion. We find that studies which build familiarity and understanding of practical drone use demonstrate the potential for more positive and informed outcomes than do more generic surveys on attitudes. The paper raises questions about the role of public acceptance research and its use in policy and calls for studies that build understanding of drones within transport environments so that stakeholders can engage in more informed debates to shape future transport provision. Graphical abstract: Image 1 Highlights: Public acceptance of drones in logistics is still to be determined. Methodological challenges impact understanding of public preferences and concerns. The public lack knowledge to engage in debates about drones in logistics. Studies are needed to show realistic parameters of drone deployment in transport settings. Scope for more informed debate on integration of drones in logistics.